Analisis Perilaku Perawat dalam Pelaksanaan Program PPI - Ningsih, Neneng Nurdianti; inayah, Iin; Oyoh, Oyoh; Asmirajati, Mira; Setiawati, Setiawati (Journal of Telenursing (JOTING), 2025)
This study aims to analyze nurses' behavior in implementing the PPI program at Anugerah Sehat Afiat Regional General Hospital, Depok City. The method used was descriptive qualitative, using Focus Group Discussions (FGDs) with purposive sampling techniques. Ten informants, consisting of five ward nurses and five members of the PPI Committee, participated. The results showed that nurses' behavior in PPI was influenced by: irregular program evaluation, supporting factors such as training and the role of superiors, constraints such as workload, limited time and PPE, varying experiences between units, interventions such as posters and feedback, perceptions of infection risk, and differing work cultures. Conclusions indicate the need for strategies to strengthen supervision, ongoing training, and cross-unit coordination to improve compliance with the PPI program. Keywords: Compliance, Patient Safety, Infection Prevention and Control (IPC), Nurses, Behavior